Verilog for digital design - Vahid, Frank (John Wiley & Sons, 2007)
Ideal as either a standalone introductory guide or in tandem with Vahid's Digital Design to allow for greater language coverage, this is an accessible introductory guide to hardware description language. Verilog is a hardware description language used to model electronic systems (sometimes called Verilog HDL) and this book is helpful for anyone who is starting out and learning the language. Focuses on application and use of the language, rather than just teaching the basics of the language